Using social media audience data to analyse the drivers of low-carbon diets. (22nd June 2021) - Eker, Sibel; Garcia, David; Valin, Hugo; van Ruijven, Bas
Abstract: Low-carbon lifestyles are key to climate change mitigation, biodiversity conservation, and keeping the Earth in a safe operating space. Understanding the global feasibility and drivers of low-carbon lifestyles requires large scale data covering various countries, demographic and socioeconomic groups. In this study, we use the audience segmentation data from Facebook's advertising platform to analyse the extent and drivers of interest in sustainable lifestyles, plant-based diets in particular, at a global level. We show that formal education level is the most important factor affecting vegetarianism interest, and it creates a sharper difference in low-income countries. Gender is a strong distinguishing factor, followed by national gross domestic product per capita and age. These findings enable upscaling local empirical studies to a global level with confidence for integrated assessments of low-carbon lifestyles. Future studies can expand this analysis of social media audience data to other consumption areas, such as household energy demand, and can also contribute to quantifying the psychosocial drivers of low-carbon lifestyles, such as personal and social norms.